Low grain weight, a new allele of BRITTLE CULM12, affects grain size through regulating GW7 expression in rice - Ye, Yafeng; Wang, Shuoxun; Ren, Yan; Yang, Huijie; Guo, Junyao; Jiang, Hongrui; Zhu, Xiaotong; Li, Wenhao; Tao, Liangzhi; Zhan, Yue; Wu, Yuejin; Fu, Xiangdong; et al. (Frontiers in Plant Science, 2022)
Grain weight is a major determinant in rice yield, which is tightly associated with grain size. However, the underlying molecular mechanisms that control this trait remain unclear. Here, we report a rice (Oryza sativa) mutant, low grain weight (lgw), which shows reduced grain length is caused by decreased cell elongation and proliferation. Map-based cloning revealed that all mutant phenotypes resulted from a nine-base pair (bp) deletion in LGW, which encodes the kinesin-like protein BRITTLE CULM12 (BC12). Protein sequence alignment analysis revealed that the mutation site was located at the nuclear localization signal (NLS) of LGW/BC12, resulting in the lgw protein not being located in the nucleus. LGW is preferentially expressed in both culms and roots, as well as in the early developing panicles. Overexpression of LGW increased the grain length, indicating that LGW is a positive regulator for regulating grain length. In addition, LGW/BC12 directly bound to the promoter of GW7 and activate its expression. Elevating GW7 expression levels in lgw plants rescued the small grain size phenotype. We conclude that LGW regulates grain development by directly binding to the GW7 promoter and activating its expression. Our findings revealed that LGW plays an important role in regulating grain size, and manipulation of this gene provides a new strategy for regulating grain weight in rice.